Effect Size of Mathematics Blended Learning Design on Increasing Mathematical Problem-Solving Ability of Polytechnic Students in the Covid-19 Pandemic Period - I Ketut Darma; I Gede Made Karma; I Made Anom Santiana; I Wayan Suastawa (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
The purpose of this study was to determine the effect size of the blended learning design on increasing the Mathematical Problem-Solving Ability of polytechnic education students during the covid 19 pandemic. The study was carried out at the Bali State Polytechnic (BSP), using a mastery-experimental approach, with a pre-test post-test design of non-equivalent control. design groups. The subjects are students in the engineering field of BSP in 2020/2021. Samples were taken purposively as many as 10 classes and divided into experimental and control groups. Data were collected using a mathematical ability test developed by the researcher. The level of validity is between 0.31 and 0.89, the reliability is 0.97, the average difficulty level is 0.41 and the discriminatory power index is between 0.25 to 0.75. Data were analyzed using t test, paired t test and N-Gain score. There is a significant difference between the average mathematical problem solving ability of students taught using the blended learning model and being taught using the full e-learning model. The blended learning model is more effective in improving mathematical problem solving abilities than the full e learning model. The effect size is very large on increasing mathematical solving abilities in learning using blended learning. The implication is that the optimal application of the blended learning design in polytechnic education during the covid 19 pandemic, the learning process becomes more effective and succeeds in improving students' mathematical problem solving abilities. ​